Oxidative stress and Liver X Receptor agonist induce hepatocellular carcinoma in Non‐alcoholic steatohepatitis model. Issue 3 (5th October 2020) - Shimizu, Yoshio; Tamura, Takafumi; Kemmochi, Akira; Owada, Yohei; Ozawa, Yusuke; Hisakura, Katsuji; Matsuzaka, Takashi; Shimano, Hitoshi; Nakano, Noriyuki; Sakashita, Shingo; Oda, Tatsuya; Ohkohchi, Nobuhiro
Abstract: Background and Aim: The incidence of non‐alcoholic steatohepatitis (NASH)‐related hepatocellular carcinoma (HCC) is progressively increasing. However, the pathophysiology and etiology of NASH progression to HCC are unknown. We hypothesized that steatosis was the key factor in NASH‐related hepatocarcinogenesis and aimed to evaluate the effects of long‐term liver X receptor (LXR) agonist stimulation on hepatic steatosis induced by a high‐fat diet and oxidative stress. Methods: We used an LXR agonist (T0901317) and CCl4 to induce hepatic steatosis and oxidative stress, respectively. C57BL/6 mice fed with a high‐fat diet were treated with either T0901317 + CCl4 (T09 + CCl4 group) or CCl4 alone (CCl4 group). T0901317 (2.5 mg/kg) and CCl4 (0.1 mL/kg) were intraperitoneally administered twice weekly for 24 weeks. Results: The liver‐to‐body weight ratio was significantly higher in the T09 + CCl4 group than in the CCl4 group. Mice in the T09 + CCl4 group exhibited abnormal lipid metabolism and NASH‐like histopathological features. Additionally, all mice in the T09 + CCl4 group developed liver tumors diagnosed as well‐differentiated HCC. The genes identified via microarray analysis were related to NASH and HCC development. Conclusions: By combining long‐term LXR agonist stimulation with oxidative stress and a high‐fat diet, we successfully reproduced liver conditions in mice similar to those in humans with NASH and progression to HCC. Our results provide new insight into NASH‐related HCC progression and therapy.